Effect of the application or coating of PGPR-based biostimulant on the growth, yield and nutritional status of maize in Benin - Adoko, Marcel Yévèdo; Noumavo, Agossou Damien Pacôme; Agbodjato, Nadège Adoukè; Amogou, Olaréwadjou; Salami, Hafiz Adéwalé; Aguégué, Ricardos Mèvognon; Adjovi Ahoyo, Nestor; Adjanohoun, Adolphe; Baba-Moussa, Lamine (Frontiers in Plant Science, 2022)
Biotechnology proposes various ecological approaches to control climatic constraints, soil fertility and plant nutrition using biological products, such as biostimulants to achieve a healthy and environment-friendly agriculture. The aim of this study was to compare the effect of biostimulant-coated maize seed and biostimulant application on the growth, yield and nutritional status of maize in Benin. The trials were set up with 100 producers spread over the whole of Benin. The experimental design was a block of three treatments with 11 replicates per Research-Development (R-D) sites. The maize varieties 2000 SYNEE-W BENIN and TZL COMP 4-W BENIN were used. The best growth (height, stem diameter and leaf area) and yield performances (thousand grains weight and grains yield) were obtained by treatments T2 (Application of biostimulant + ½ NPK-Urea) and T3 (Seed coating with biostimulant + ½ NPK-Urea) compared to the farmers' practice (T1). A significant difference was observed between the different treatments for height, leaf area, 1000 grains weight and maize-grain yield. From one Research-Development site to another, a significant difference was also observed for all parameters. The treatment- Research-Development site interaction was also significant in most areas. The applied or coated biostimulant improved the uptake of nitrogen, phosphorus and especially potassium with higher significant difference compared to the recommended dose of mineral fertilizer. The two techniques of using the biostimulant combined with the half-dose of mineral fertilizer gave the better growth, yield and nutritional status compared to the farmers' practice in all areas study. This biostimulant can be used to ensure food security and sustainable agriculture in Benin.